Slam: periferia, pós-memória e identidade - Fernanda Vilar (Confluenze, 2020)
The peripheral writing of Lisbon influences the articulation of an inclusive history of colonialism in Portugal, and broadly in contemporary Europe. The emergence of Slam Poetry fulfills a necessary task in relation to the European colonial past, still strongly marked (in its collective unconscious) by the ghosts of traumatic pasts yet to be elaborated. The way the poet raquellima uses the post-memory of colonization provides a privileged point of view for a critical study because it allows to question the concept of coloniality to fabricate peripheral identities anchoring her particular history in a more global one.